(3YfhGf GdoeQbUGJ hGdoeWQHGJs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s ((3CMeO Hf eMeO Hf EHQGgje GdCRgQj GdMfaj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj TQa GdEfSGf, Ydi SGFQ CfhGY GdMjhGf HfWb GddSGf heRLJ GdeQbUGJ HGdeWQHGJ ajg eRL GdMeQI HGdHjGV aj GdNOhO, haUdJ eG Hjf aVdGA GdTQb haVdGA GdZQH s
(3BNQgG (B:s
(3YLHJ dg hgh GdCUjd HYQag XdGe hHjf GdfGXQjf UHGM JeJ GdeQbUGJ hGdeWQHGJ s
(3UaMI GdYfhGf ePgHI HQSe GdRjfj GdNRQLjs
(3fSNI NRGFfjI fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
Keywords: (3GdCOHs